Aberrant origin of the occipital artery from the internal carotid artery: utility of the occipital tap maneuver - Enrico Premi, MD (Elsevier, 2021)
We have described a case of a suspected transient ischemic attack with a double lumen potentially resembling a dissection of the internal carotid artery on Doppler ultrasound. The identification of an arterial branch from the internal carotid artery and flowing near it using magnetic resonance imaging suggested an aberrant origin of an ascending pharyngeal artery or occipital artery. Performance of the occipital tap maneuver in the occipital artery perfusion territory demonstrated a reflected flow in the double lumen, supporting the aberrant origin of the occipital artery from the internal carotid artery. The occipital tap maneuver can represent an easy-to-do procedure to distinguish anatomic variants and study double-lumen findings.